Single session intermittent theta-burst stimulation on the left premotor cortex does not alleviate freezing of gait in Parkinson's disease. (15th August 2016) - Tard, Céline; Devanne, Hervé; Defebvre, Luc; Delval, Arnaud
Highlights: rTMS over Pre-motor cortex could modify FoG in PD. FoG occurrence, gait initiation and continuous gait were recorded. iTBS of the left premotor cortex does not alleviate FoG in PD. Abstract: Objective: To investigate the efficiency of intermittent theta-burst stimulation (iTBS) to alleviate the symptoms of freezing of gait (FoG) in Parkinson's disease (PD). Methods: We performed a cross-over, sham-controlled study of patients with severe PD, bilateral motor signs and debilitating, severe FoG, that was levodopa-sensitive but not controlled by optimal dopatherapy. We applied iTBS to the left premotor cortex and measured FoG, gait initiation and continuous gait, before and immediately after the iTBS session. All patients received sham and true iTBS with a one-week interval and in randomized order. Results: 15 patients were included in the study. Recordings were performed under usual medication and all patients always showed unresponsive freezing. The pre- and post-stimulation gait trajectories did not differ in terms of the mean trajectory completion time or the percent time with FoG. The percent time with FoG was 6% greater after sham stimulation and 3% lower after iTBS (p > 0.05). Visual cueing modified gait initiation and continuous gait but these latter were not influenced by rTMS. Conclusions: The present study provides Class I evidence that iTBS of the left premotor cortex does not alleviate FoG in PD.